Parsing polarization squeezing into Fock layers - Müller, Christian; Madsen, Lars S.; Klimov, Andrei B.; Sanchez-Soto, Luis L.; Leuchs, Gerd; Marquardt, Christoph; Andersen, Ulrik L. (Physical Review A, 2016)
We investigate polarization squeezing in squeezed coherent states with varying coherent amplitudes. In contrast to the traditional characterization based on the full Stokes parameters, we experimentally determine the Stokes vector of each excitation subspace separately. Only for states with a fixed photon number do the methods coincide; when the photon number is indefinite, we parse the state in Fock layers, finding that substantially higher squeezing can be observed in some of the single layers. By capitalizing on the properties of the Husimi Q function, we map this notion onto the Poincaré space, providing a full account of the measured squeezing.
CRIS-Team Scopus Importer:2022-06-05